2006
DOI: 10.1136/jech.2005.039792
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic determinants of health related quality of life in childhood and adolescence: results from a European study

Abstract: There is evidence to suggest that exposure to low parental educational status may result in a decreased HRQoL in childhood, whereas reduced access to material (and thereby social) resources may lead to a lower HRQoL especially in adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
245
10
25

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(320 citation statements)
references
References 33 publications
40
245
10
25
Order By: Relevance
“…We can also examine the extent to which well-being is affected by gender, health status, age and the presence of children. Many studies have found that socio-demographic factors play an important role in explaining inter-individual variability in well-being 14,15,16 and depressive symptoms 17,18 , as well as in physical morbidity 19,20,21,22 .…”
Section: Socio-demographic Factors and Labour Market Characteristicsmentioning
confidence: 99%
“…We can also examine the extent to which well-being is affected by gender, health status, age and the presence of children. Many studies have found that socio-demographic factors play an important role in explaining inter-individual variability in well-being 14,15,16 and depressive symptoms 17,18 , as well as in physical morbidity 19,20,21,22 .…”
Section: Socio-demographic Factors and Labour Market Characteristicsmentioning
confidence: 99%
“…Although it may be assumed that public social security systems, as they exist in Germany, ensure universal access to health care services, inequalities have been described in countries with well-developed social security systems [1,5,8,10,11,18,19]. For example, the participation rate in regular health check-up examinations during childhood which are nationally recommended in Germany and covered by the health insurance has shown to be up to 20 % lower in families with a low socio-economic status compared to families with a high socio-economic status [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the educational level of the parents and family wealth (material factors such as computers, leisure, books, etc.) are relevant to predict well-being in adolescence (Von Rueden et al, 2006). This is an important aspect that deserves attention from policy makers and social entrepreneurs, since low socioeconomic status among parents can contribute to poor childhood health outcomes (Perreira and Ornelas, 2011).…”
Section: Discussionmentioning
confidence: 99%